THE CORRELATION BETWEEN STUDENTS’ SPEAKING ANXIETY AND SPEAKING ABILITY AT SMA NEGERI 4 BAUBAU - Nety Nety; Bagas Purnomo (English Education Journal, 2023)
The problem statement of this research was whether there was a significant correlation between students’ speaking anxiety and speaking ability at SMA Negeri 4 Baubau. This research aimed to determine whether there was a significant correlation between students’ speaking anxiety and speaking ability at SMA Negeri 4 Baubau. The method of this thesis was an ex post facto method. The population of this research was the grade eleven students at SMA Negeri 4 Baubau in the school year of 2022/2023 which consisted of a total population was 287 students. The technique of sample used in this research was simple random sampling and the sample of the research was 50 samples. The research was carried out by using a questionnaire and a test as the instruments. The questionnaire was used to find out the category of students’ speaking anxiety and the test was used to find out the category of students’ speaking ability. The data obtained using the questionnaire and test then were analyzed by descriptive statistical analysis, prerequisite analysis, and inferential statistical analysis. Based on the result of this research, it concluded that the Sig. value was 0.001. Because of the Sig. value was higher than 0.05, which meant that Ha was accepted and H0 was rejected. It meant that there was any significant correlation between students’ speaking anxiety and speaking ability on grade eleven students at SMA Negeri 4 Baubau.